Teacher Coaching Model in Improving Students' Qur'an Reading Ability at MTs Istiqomah Muara Teweh, North Barito Regency - Huda, Muhammad Fadhil; Ajahari; Saiful Lutfi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2025)
This study was conducted to describe the teacher coaching model in improving students' Qur'an reading ability at MTs Istiqomah Muara Teweh, North Barito Regency. A descriptive qualitative approach was used in this study with data collection techniques through observation, interviews, documentation, testing, and data validation through triangulation techniques. From the results of the study, the coaching model chosen is the Tartil model, which uses the Iqro method and the ummi method in accordance with the method mastered by the teacher and the suitability for students. There are three main stages in the implementation of coaching, which include the opening session, the core session, and the closing session, with an emphasis on proper pronunciation, the law of tajweed, and reading fluency. Supporting factors for coaching success include motivation and support for students and adequate infrastructure, while the main obstacles come from a lack of coaching time and fluctuations in students' emotions. A 24-day trial involving nine grade VII A students showed that eight students experienced significant improvements in Qur'anic reading ability, especially in the legal aspects of reading, and proper short duration (mad). This study concludes that a teacher coaching model that is structured and adjusted to the level of ability of students in an organized manner can improve students' ability to read the Qur'an in accordance with the rules of tajweed